Effects of irrigation rate on the growth, yield, nutritive value, and water use efficiency of Carrot (Daucus carota) and Broccoli (Brasiola oleracea) - Ludong, Daniel Peter M. (Curtin University, 2008)
The effects of differential irrigation treatments on the water use of broccoli (c.v. Indurance) and carrots (c.v. Stefano) were studied in the rainy, winter season from July to September 2006 and in the dry, summer period from November 2006 to March 2007, respectively. Broccoli and carrots are produced on the Swan Coastal Plain region on Grey Phase Karrakatta Sand. Such soils generally have water holding capacities as low as 10 to 13%. This soil is typical to the Swan Coastal Plain and requires irrigation to be applied at rates of up to 150% of class A pan evaporation (Epan) to optimise growth and quality.High spatial uniformity (an average of 90%) of water distribution (DU) was achieved with the sprinkler irrigation system. The average irrigation water use efficiencies (Eu) in both the experiments were relatively high, at 78% and 95% in broccoli and carrot trials, respectively. The numerous rainy days during the winter season affected the results of water application efficiencies (Ea) of the broccoli experiment, which ranged from 35% to 43%. This contrasted with the carrot experiment where the water application efficiencies (Ea) of the 100% Epan and Crop Factor (CF) treatments were 81% and 78%, respectively. For the carrot experiment the water application efficiencies for the 100% Epan and crop factor treatments were 14% higher than the 150% Epan treatment. These results indicate that the sprinkler irrigation systems in both experiments showed good performance makes the system suitable for experimental purposes and also for vegetable production on soils of this nature.Despite the differences in irrigation volume, soil water contents remained very high and did not differ among treatments in both the experiments. The differential soil water stress index (DSWSI) for the 100% Epan (T1) and variable water replacement (VR) (TVR) treatments ranged from 0.74 to 1.71 for both broccoli and carrot trials. There were only small soil water tension differences among all the irrigation treatments and ranged from -2.4 kPa to -7.6 kPa, which was within the range between saturation and field capacity for sandy soil (0 to -10 kPa).In the broccoli experiment, even though the 150% Epan (T2) irrigation treatment received 46% and 61% more irrigation than the 100% Epan (T1) and variable water replacement (TVR) irrigation treatments respectively, the treatments appeared to be largely negated by the high incidence of rainfall during the growing season. For example, the total depth of water application at 150% Epan was 13.9% and 17.2% greater than 100% Epan and TVR treatments respectively. As such the yield, biomass components and nutritional value (ascorbic acid and carotenoid content) did not vary among the treatments. However, irrigation was still required based on the set scheduling parameters and when considered in isolation of rainfall the irrigation crop water use efficiency (WUEi) on T1 and TVR treatments increased by 1.6-fold compared to T2 treatment.For the carrot experiment the total depth of water application (rainfall and irrigation) for the 150% Epan treatment was 33% and 23% greater than at 100% Epan and Crop factor (CF) treatments, respectively. The yield (carrot roots) on a fresh weight basis (FW) for plants irrigated with the 150% of Epan and Crop factor (CF) treatments were 16% and 20% higher than the yield for plants irrigated with the 100% Epan treatment. Total (root and shoot) fresh weight of carrot plants irrigated For the carrot experiment the total depth of water application (rainfall and irrigation) for the 150% Epan treatment was 33% and 23% greater than at 100% Epan and Crop factor (CF) treatments, respectively. The yield (carrot roots) on a fresh weight basis (FW) for plants irrigated with the 150% of Epan and Crop factor (CF) treatments were 16% and 20% higher than the yield for plants irrigated with the 100% Epan treatment. Total (root and shoot) fresh weight of carrot plants irrigated with the CF treatment was 17% higher than the total fresh weight of plants irrigated with the 100% Epan treatment. However, there were no significant differences between irrigation treatments for root and total (root and shoot) mass on a dry weight basis and the ratio of carrot root to shoot, on a fresh and dry weight basis. The root lengths for plants grown with the CF and 150% Epan irrigation treatments averaged 30 cm, and were 14% larger than the root lengths for the 100% Epan treatment. The plant height for plants grown with the CF irrigation treatment was 6% higher than at the 100% Epan irrigation treatment and leaf length at the CF irrigation treatment was 12% greater than at the 150% Epan irrigation treatment.The root diameter and leaf width of carrots were not significantly different for all treatments. There were no significant differences in ascorbic acid and total carotenoid content of carrot roots among the three irrigation treatments. The average values of antioxidant content from diphenylpicrylhydrazyl (DPPH) scavenging, ARP (anti radical power) and total trolox equivalent antioxidant capacity were 44.83%, 0.8789 and 1.056μmol TE/g, respectively. The reduction of the irrigation level treatment from the 150% Epan water replacement to the 100% Epan water replacement increased the percentage of the DPPH scavenging by 1.55%, and total antioxidant capacity (AOC) and ARP activities by 4.19%.On a dry weight basis, the crop water use efficiencies (WUE) (irrigation plus rain water) of carrot plants irrigated with the 100% Epan and CF treatments, were the same (0.013 g/mm). However, these were 30% greater than the WUE values of carrots irrigated with the 150% Epan treatment. On a fresh weight basis, the WUE of carrot plants irrigated with the 100% Epan and CF (0.120 and 0.132 g/mm) treatments were 14% and 26% greater than the WUE of carrot plants irrigated with the 150% Epan treatment, respectively.An example of the diurnal trends of the carrot’s physiological responses to the irrigation treatments showed that on average, the rate of photosynthesis, stomatal conductance and intercellular CO2 for carrot plants grown with the 150% Epan treatment was higher than the rate of photosynthesis, stomatal conductance and intercellular CO2 at both the 100% Epan and CF treatments. However, not all the physiology measurements showed a significant difference among all the treatments. The variation in the physiological measurements was predominantly influenced by the change of temperature during the diurnal hours.This study has proven the hypothesis that, on a free draining sandy soil, the irrigation treatments did not affect the growth and yield. However, there was a potential to reduce irrigation volumes from standard industry levels to maximise the WUE without decreasing the yield and crop quality, especially for broccoli and carrot, in Western Australia.